The Future of Cryptocurrency - Kanika Thakur; Dr. Priya Satsangi; Deepanshu Kumar; Ujjwal Saxena (International Journal of Engineering and Management Research, 2023)
Cryptocurrency is a peer-to-peer network for exchange. It is digital and also known as virtual currency that uses cryptography a security related coding system. Most of the governments across the world are in the dilemma of making cryptocurrecy as legal. The regulation of official digital currency proposed to introduce in centralized way by various banks in an around the world. Unlike equity, this currency has no regulation regarding the trade in decentralized market due to no underlining in fundamentals and financial values. This money has a good future in terms of technological advancement in circulation and controlling of money with centralized controlling system. Central based digital currency (CBDC) is continuously doing a pilot survey from Dec 1st 2022 in major cities to exactly know the channelization if this currency. Major dialogues are going on as decentralized currency is not safe for any country’s economic system. Digital money can either be centralized, where there is a central point of control over the money supply by a central bank or decentralized where the control over the money supply is predetermined or agreed upon self-governing. The Mining of crypto currency is done through cryptography in which specialized computers are used for recording the transactions. The young Indian especially in tier 2 and tire 3 cities are inspired through this currency. Financial literacy and awareness are of paramount importance in order to have a healthy skin in the crypto game. The trading amounts to gambling might not hold much steam because success in any market depends on informed entries, caution risk-taking and strategic exits. Bitcoin is the first and most prevalent Cryptocurrency till the date. Now in the information technology world in which we can interact with each other for exchange without a regulatory body or centralized system, Cryptocurrency is an example of digital change accepted by the people. In this paper we have analyzed the effects of crypto currency and its impact during pandemic. The whole study of this currency is divided in 7 continents and bifurcated according to legal, illegal, banned, prohibited and restricted countries according to the use. And also the initiative by the Indian government regulation related to crypto currency.